The Simpsons and their mathematical secrets - Singh, Simon Lehna, 1964- (New York : Bloomsbury, 2013)
"Simon Singh, author of the bestsellers Fermat's Enigma, The Code Book, and The Big Bang, offers fascinating new insights into the celebrated television series The Simpsons: That the show drip-feeds morsels of number theory into the minds of its viewers--indeed, that there are so many mathematical references in the show, and in its sister program, Futurama, that they could form the basis of an entire university course. Recounting memorable episodes from "Bart the Genius" to "Homer3," Singh brings alive intriguing and meaningful mathematical concepts--ranging from the mathematics of pi and the paradox of infinity to the origin of numbers and the most profound outstanding problems that haunt today's generation of mathematicians. In the process, he illuminates key moments in the history of mathematics, and introduces us to The Simpsons' brilliant writing team--the likes of David X. Cohen, Al Jean, Jeff Westbrook, and Stewart Burns, all of whom have various advanced degrees in mathematics, physics, and other sciences. Based on interviews with the writers of The Simpsons and replete with images from the shows, facsimiles of scripts, paintings and drawings, and other imagery, The Simpsons and Their Mathematical Secrets will give anyone who reads it an entirely new insight into the most successful show in television history"--
Includes bibliographical references and index.
Keywords: Simpsons (Television program) -- Miscellanea; Art -- Popular Culture; Mathematics -- Miscellanea; Mathematics -- General; Social science -- Popular Culture; The Simpsons (televisieprogramma).; Wiskunde